British Society of Gastroenterology (BSG) guidelines for management of autoimmune hepatitis. Issue 12 (13th July 2011) - Gleeson, Dermot; Heneghan, Michael A
Abstract : Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease which, if untreated, often leads to cirrhosis, liver failure and death. Major advances were made in its management based on controlled trials performed in England and the USA in the 1970s and 1980s. Unfortunately, in recent decades there has been a dearth of controlled clinical trials and, thus, many questions regarding the optimal management of this disease remain unanswered. Many promising newer immunosuppressive therapies await formal comparison with standard therapies and also many important details in relation to the application of standard therapies remain unclear. These guidelines describe the optimal management strategies in adults based on available published evidence, including the American Association for the Study of Liver Diseases practice guidelines for the diagnosis and treatment of AIH published in 2002 and recently updated.